Pengaruh Profitabilitas, Likuiditas, dan Struktur Modal Terhadap Nilai Perusahaan (Studi Kasus Pada Perusahaan Manufaktur Sub Sektor Makananan dan Minuman Yang Terdaftar Di Bursa Efek Indonesia Tahun 2017-2020) - Dimas Fathur Fauzi Juniawan; Budi Wahono; Nurhidayah Nurhidayah (UNIVERSITAS ISLAM MALANG, 2022)
Abstract This study holds back nothing productivity, liquidity, and capital construction on firm worth in the Food and Drink Sub-Area Assembling Organizations Recorded on the Indonesia Stock Trade in 2017-2020. The general population in this study are all Food and Refreshment Sub-Areas Recorded on the Indonesia Stock Trade in 2017-2020 with a sum of 31 organizations. Testing procedure utilizing purposive inspecting technique got information tests upwards of 15 financial organizations. The strategy for information assortment in this examination utilizes the technique for information documentation recorded in the yearly report (IDX). The information investigation method in this study utilized different direct relapse with SPSS ver 16 programming. The outcomes showed that all the while productivity, liquidity, and capital construction affected firm worth. To some degree, productivity significantly affects firm worth. Liquidity and capital construction meaningfully affect firm worth. Keywords: Firm Worth, Productivity, Liquidity, Capital Construction